2013
DOI: 10.1155/2013/736275
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Bed Adsorption Study on Phosphate Removal Using Nanosized FeOOH‐Modified Anion Resin

Abstract: Removal of phosphate from solution using nanosized FeOOH-modified anion resin was studied in fixed bed column. Effect of bed height and flow rate on the breakthrough curves were investigated. Longer breakthrough time was obtained by increasing the bed height and decreasing the flow rate. Bed service depth time (BDST) model was applied to recount the relationship between bed service time and bed height. The value ofN0was calculated to be 21.4 g/L. Yoon-Nelson model, which fitted well with the experimental data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The BDST model originally developed by Bohart and Adams was applied to represent the relationship between service time and bed depth. This model is based on the surface reaction rate theory and assumes that the rate of adsorption is proportional to the fraction of adsorption capacity remaining on the sorbent . It was reported that the BDST model was applicable to describe the initial part of the breakthrough curve, approximately just up to the breakthrough point or 10 to 50% of the saturation points.…”
Section: Resultsmentioning
confidence: 99%
“…The BDST model originally developed by Bohart and Adams was applied to represent the relationship between service time and bed depth. This model is based on the surface reaction rate theory and assumes that the rate of adsorption is proportional to the fraction of adsorption capacity remaining on the sorbent . It was reported that the BDST model was applicable to describe the initial part of the breakthrough curve, approximately just up to the breakthrough point or 10 to 50% of the saturation points.…”
Section: Resultsmentioning
confidence: 99%
“…3− /g) as shown by the result of this study. Other studies using materials such as impregnated skin split waste [5], hybrid fibres [19], and synthetic materials [26] showed results within the range 66.4 to 220.8 mg PO 4 3− /g. Akaganeite also showed better results (51.8 to 71.5 mg PO 4…”
Section: Effect Of Particle Size On Adsorption Isothermmentioning
confidence: 93%
“…Several ferric hydroxide sizes below the usual GFH size range (1 mm) have been used as promising materials to increase the kinetics and adsorption capacity of phosphate in stirred batch tests, as it happens, for instance, in the case of activated carbon with micro-contaminants [22,23]. The procedures involved for size reduction of the adsorbent include sieving of GFH [24], grinding [1,17], or the synthesis and use of nano-sized materials [19,[24][25][26]. From these references, only one study was centered in the role of reduced size particles obtained from the same bulk GFH on the adsorption of phosphate (equilibrium and kinetics) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Natural polysaccharide chitosan, a derivative of chitin [8][9] has been known for its unique properties due to the existence of high content of amino and hydroxyl functional groups in its molecules that contribute in the process of adsorption [10]. Moreover, chitosan is a nontoxic, biodegradable, and biocompatible polymer, which can be used as a wound dressing, tissue engineering, and drug delivery systems [11].…”
Section: Introductionmentioning
confidence: 99%